Emphysematous pyelonephritis: eight case reports and literature review - Jiang, Du; Taoyu, Yang; Tao, Wu; Xianyue, Peng; Chenren, Gou; Guobiao, Liang (Frontiers in Medicine, 2025)
ObjectiveThis study aims to discuss and summarize the diagnosis and treatment of emphysematous pyelonephritis (EPN).MethodsRetrospective medical records review of all patients diagnosed with EPN from January 2017 to June 2023 in our hospital were analyzed. A total of eight patients (three males and five females) were enrolled. The mean age was 49.38 ± 3.48 years. Among them, one case was complicated by sepsis, two by emphysematous cystitis, two by chronic renal failure, four by diabetes, and five by urolithiasis. Upon admission, all patients received aggressive antimicrobial therapy. Surgical interventions consisted of drainage procedures tailored to each patient's specific condition along with management for upper urinary tract calculi present. Clinical data were analyzed in depth and compared with the previously published studies.ResultsAll patients complied with the protocol of catheter removal as scheduled and were discharged after complete recovery. No recurrence of infection was recorded during the follow-up.ConclusionsMost EPN patients suffer from severe and complex medical conditions. Selecting an appropriate surgical drainage strategy can significantly reduce the rates of infection recurrence, nephrectomy and mortality, thereby improving the patient's prognosis.